Developing the Adolescent Career Success Instrument (ACSI): A Rasch Model analysis - Hamdan, Amirul Hazmi; Supriatna, Mamat; Yudha, Eka Sakti (Universitas Negeri Padang, 2022)
Career success is an individual's ability to achieve self and work success. There are various instruments to determine individual career success. However, there has not been a career success instrument specifically developed for adolescents. This study aims to develop and validate The Adolescent Career Success Instrument (ACSI) using the Rasch model analysis. Participants in this study consisted of 3 guidance and counseling experts for the constructed test, 4 students for the readability test, and 106 students (33 male students and 73 female students) from high school for the empirical test. ACSI reliability test results show that the item reliability is 0.90 in a good category, while the personal reliability is 0.85 in a good category. Cronbach's alpha value is 0.91 in the very good category. The results of the ACSI analysis using the Rasch model showed that 49 reliable items could be used to measure adolescent career success.